Supervisi Klinis untuk Meningkatkan Kemampuan Guru di Madrasah Ibtidaiyah - Dodo, Dodo (Jurnal Garasi Buku dan Obrolan Keilmuan, 2023)
This study aims to explain the efforts of supervisors in improving teacher professionalism through clinical supervision in Madrasah Ibtidaiyah (MI). Clinical supervision is a form of service provided by school / madrasah supervisors to teachers who face difficulties or problems in learning, with the principle of supervisory operational assistance to teachers in learning, not orders or instructions. This study used a qualitative approach with a focus on six MI teachers who were selected deliberately using purposive sampling techniques. Data were collected to analyze teachers' experiences and perceptions of clinical supervision and its impact on their professional ability to teach. The results showed that professional supervisors have an important role in providing guidance and coaching to teachers. With the help of supervisors, teachers can overcome the problems at hand, and become more independent, creative, motivated, and innovative in their teaching tasks. Thus, professional supervisors contribute to improving the quality of education in madrasas. Some recommendations to improve the effectiveness of clinical supervision include conducting studies on teacher needs and problems, involving teachers in the analysis of supervision materials, preparing technical guidelines for clinical supervision, using a collaborative approach, and applying the concept of Quality Assurance (QA) in supervisory tasks. It is hoped that this recommendation can increase the effectiveness of clinical supervision in improving the professional ability of teachers in other madrasahs.